Demographic Distribution of Head-Neck Carcinoma of ENT Oncology Department of NICRH in 2020 (Bangladesh Journal of Otorhinolaryngology, 2022)
Background: Head and neck cancer (HNC) comprises a diverse group of oncological entities, originating from various tissue types and organ localizations, situated in the topographical regions of the head and neck (H&N). This single institution retrospective study was aimed at establishing the HNC patient geographic & demographics and categorizing the individual incidence of H&N malignancies, regarding their organ of origin.Objectives: To identify the age Distribution, Occupation, Disease Specific Gender Distribution, Disease Incidence of different types of Head-Neck Cancer according to geography of Bangladesh.Methods: This retrospective data analysis to asses age, occupation, Disease Specific Gender Distribution, Disease Incidence of different types of Head-Neck Cancer diagnosis, using medical records data of 3047 Head & Neck Cancer patients from National Institute of Cancer Research & Hospital designated cancer center in Bangladesh in 2020. All new cases of Head- Neck Cancer patients attend in ENT Oncology Department included in this study. Old cases, who were attend for follow up excluded from study.Results: Total 3047 new patients were included. Thyroid Carcinoma 365(12%), Sinonasal 212(7%), Salivary gland Carcinoma 121(4%), Oral Cavity 303(9.9%), Oropharyngeal Carcinoma 243(8%), Hypopharynx 457(15%), Larynx 761(25%), Nasopharyngeal Carcinoma 91 (3%), Carcinoma Unknown Primary 304(10%), Lymphoma 154(5.1%), Others 36(3.2%). Male: Female 3:2.Conclusion: Head & Neck Cancer (HNC) is common cancer in Bangladesh. Functional & cosmetic deformities occur in head & neck cancer. The reported single institution results appear representative of the national incidence and characteristics of HNC.Bangladesh J Otorhinolaryngol 2022; 28(1): 68-77